(untitled) (Journal of The Colloquium for Information Systems Security Education, 2020)
This innovative research project chronicles how cybersecurity professionals and professors rate recent cybersecurity graduates in the components of Cybersecurity Competency Model. Noteworthy findings included that information technology graduates exhibit poor reading, writing, and some communication skills; there was a statistically significant difference between the two groups in their thoughts on the importance of mathematics; and there was a significant difference between the two groups pertaining to (a) planning and organization and (b) working with tools of technology.